2022
DOI: 10.1002/tox.23613
|View full text |Cite
|
Sign up to set email alerts
|

Selenium deficiency aggravates bisphenol A‐induced autophagy in chicken kidney through regulation of nitric oxide and adenosine monophosphate activated protein kinase/mammalian target of rapamycin signaling pathway

Abstract: Bisphenol A (BPA), a phenolic compound, is harmful to humans and animals as its residue in the water threatens multiple organs, especially the kidney. Low selenium (Se) diets are consumed in many regions of the world, and poor Se status has exacerbating effect on toxicity of several environmental chemicals. Here, we described the discovery path of Se deficiency aggravation on autophagy in BPA treated chicken kidney through regulating nitric oxide (NO) and adenosine monophosphate activated protein kinase (AMPK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Kidneys play an important role in selenium homeostasis [ 41 , 52 ]. Selenium is often used as a protector against nephrotoxic effects of chemicals (e.g., [ 53 , 54 , 55 , 56 , 57 ]). However, it has been shown that rising doses of Se NPs have an increasingly pronounced nephrotoxic effect and accumulate in renal tissues [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kidneys play an important role in selenium homeostasis [ 41 , 52 ]. Selenium is often used as a protector against nephrotoxic effects of chemicals (e.g., [ 53 , 54 , 55 , 56 , 57 ]). However, it has been shown that rising doses of Se NPs have an increasingly pronounced nephrotoxic effect and accumulate in renal tissues [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…BPA exposure activated autophagy-related proteins ( ATG5 , ATG7 and MAP1LC3B/LC3B ) and decreased the expression of NRF-2 and HO-1 proteins [ 162 , 163 , 164 , 165 ]. BPA also activated the AMPK/mTOR (The 5′-adenosine monophosphate-activated protein kinase and mammalian target of rapamycin) signaling pathway, which triggers P62/Lc3/Beclin1 signaling, leading to the formation of autophagosomes and autolysosomes, and ultimately, stimulating autophagy in renal cells [ 166 , 167 ]. BPA exposure down-regulated the expression of PI3K (phosphatidylinositide 3-kinases) and AKT (protein kinase B) and activated the Bcl/Bax-Caspase 9-Caspase 3 (B-cell lymphoma/BCL2-Associated X-Caspase 9-Caspase 3) signaling pathways, leading to apoptosis and necrosis of renal cells [ 168 ].…”
Section: Bisphenol Amentioning
confidence: 99%